Design Equations for Mixed-Mode Fracture of Dental Ceramic–Cement Interfaces Using the Brazil-Nut-Sandwich Test - Manan, David Tamim; Kim, Jeongho; de Melo, Renata Marques [UNESP]; Zhang, Yu (ASME International, 2021)
Dental interfaces are subject to mixed-mode loading. This study provides practical guidance for determining interfacial fracture toughness of dental ceramic systems. We address interfacial fracture of a composite resin cement sandwiched between two dental ceramic materials. Emphasis is placed on sandwich disc specimens with cracks originating from elliptical-shaped flaws near the center, for which analytical fracture mechanics methods fail to predict. The interaction integral method is used to provide accurate finite element solutions for cracks with elliptical-shaped flaws in a Brazil-nut-sandwich specimen. The developed model was first validated with existing experimental data and then used to evaluate the three most widely used dental ceramic systems: polycrystalline ceramics (zirconia), glass-ceramics (lithium disilicate), and feldspathic ceramics (porcelain). Contrary to disc specimens with ideal cracks, those with cracks emanating from elliptical-shaped flaws do not exhibit a monotonic increase in interfacial toughness. Also, interfacial fracture toughness is seen to have a direct relationship with the aspect ratio of elliptical-shaped flaws and an inverse relationship with the modulus ratio of the constituents. The presence of an elliptical-shaped flaw significantly changes the interfacial fracture behavior of sandwich structures. Semi-empirical design equations are provided for fracture toughness and stress intensity factors for interfacial cracks. The developed design equations provide practical guidance for determining interfacial fracture toughness of selected dental ceramic material systems. Those equations take into account four critical factors: size of the elliptical flaw, modulus ratio of constituent materials, loading angle, and applied load.
Keywords: Brazil-nut-sandwich test; ceramic restorations; ceramics; composite resin cements; elastic behavior; finite element analysis; fracture toughness; interfacial fracture; intermetallics; mechanical behavior; metals; polymers; stress intensity factors; their composites